(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
Lourenço, Jamily Bonisson Abreu Brunetti. Popular initiative bills in the municipality of São Mateus. Dissertation (Professional Master in Science, Technology and Education). Vale do Cricaré College, São Mateus, ES, 2020. Popular participation in Brazil’s political decisions, although advocated by the current constitutional text, still remains a reality disassociated from most citizens. Actions of this nature seem to be limited to the electoral period, when, by obligation, society is compelled to go to the polls. The fact is that there are several constitutional mechanisms created to guarantee the sovereignty of the people, one of which is the initiative of bills through the popular route. This institute, still not widespread, applies to both the federal, state and municipal aspects. Based on this reality and considering the importance of microparticipation as an elementary tool in the awareness process that leads to macroparticipation, the municipality of São Mateus, located in the north of the state of Espírito Santo, was chosen as the protagonist of the research. Through questionnaires applied to the Mateense population, civil society entities and interviews with representatives of the local legislature, it was possible to glimpse the real engagement of the citizen in the popular initiative of municipal law projects, the general objective of the research. Specific objectives were also revealed: number of laws of popular initiative cataloged; popular knowledge on the subject and, finally, produce an educational booklet aimed at the correct way for citizens to use the existing democratic mechanism. Keywords: Citizen. Participatory democracy. Law Initiative. Sao Mateus.